A novel wound dressing material for full-thickness skin defects composed of a crosslinked acellular swim bladder - Zhang, Lifeng; Li, Yan; Jiang, Wei (Frontiers in Materials, 2022)
The repair of widely pervasive skin defects remains a daunting challenge. Previous research on skin defects has applied artificial skin, although this is limited by high cost and complex fabrication. Biomaterials have attracted much attention in recent years due to their accessibility and excellent biocompatibility. We designed a novel cell-scaffold material for wound dressing using swim bladders; the mechanical properties of these could be enhanced by EDC/NHS crosslinking. This material possesses many advantages, including adequate porosity, high mechanical strength, and good thermal stability. In particular, swim bladders after EDC/NHS crosslinking have an increased denaturation temperature and higher tensile strength, along with the ability to be harmlessly colonized in the wound sites of rabbit models, followed by rapid vascularization and cell growth with mild inflammatory reactions. The successful implantation of swim bladders proves that this cell scaffold with its unique features can be an outstanding wound dressing material.